The Effectiveness of The Integrated Home-Based Program on Blood Pressure, Body Fat Percentage And Eating Behavior among Uncontrolled Hypertensive Patients - อัครธนพล ปริศนา; ดีนาน อาภรณ์; ศรีสุริยเวศน์ รุ่งรัตน์ (Journal of The Royal Thai Army Nurses, 2019)
The study’s aimed to determine the effects of an integrated home-based (IHB) program on blood pressure, body fat and eating behavior among patients with uncontrolled hypertension. The IHB was based on evidence-based practices and self-regulation concept. Program strategies included nurse counseling, goal setting, health education, home blood pressure monitoring, self-appraisal in making progress by an action plan, revision of goals and action plans, and telephone support within six weeks. Eighty patients with uncontrolled hypertension who met the inclusion criteria were recruited to participate in the study. A quasi-experimental design was used by assigning 40 participants to the IHB group and other 40 to the control group. Participants in the experimental group received IHB program as an intervention and usual care, while the control group received usual care. Blood pressure, body fat and the three-factors eating questionnaire (TFEQ) were measured at baseline, week 7 and week 11. Descriptive statistics, chi-square, paired t-tests, and Repeated Measures ANOVA were used to analyze the data. The results found that majority was female. Mean age was 60.9 years, and average duration of hypertension was 4.4 years. The IHB group had significantly lower systolic and diastolic blood pressures, lower percentages of body fat, and improved eating behavior compared to the baseline and the control group. The results suggested that The IHB program was benefits for uncontrolled HT and could be used in community setting.